A Woman’s Identity as Depicted in Angelou’s Poem “Woman Work” - Ayu Shadrina Saraswati (Lexicon, 2012)
This article analyzes Maya Angelou‟s poem “Woman Work”. This poem talks about identity which is described by Maya Angelou through her feelings and ideas. The objective of this research is to study Maya Angelou‟s search of identity which is depicted through the poem.This article uses an expressive approach because this approach is the most suitable for learning the poet‟s perspective on woman identity through her works. Library research is employed to support the analysis.The result of the analysis implies that the speaker‟s position is a woman who has a role in society as a mother, worker and slave. The speaker carries out all jobs in the house and outside. However, the speaker expresses a process of her journey to find her identity which is reflected in the poem. The speaker tries to prove that identity is an important part of her qualities that must be maintained.In this poem the speaker indicates that she becomes a woman who is more confident and proud. It is the result of her process of maturity that is expressed by her that makes her realizes the truth of her identity. The speaker reveals the process of her life that is faced by her to display that she is a strong woman.